From features to dimensions: cognitive and motor development in pop-out search in children and young adults - Grubert, Anna; Indino, Marcello; Krummenacher, Joseph (Frontiers in Psychology, 2014)
In an experiment involving a total 124 participants, divided into eight age groups (6-, 8-, 10-, 12-, 14-, 16-, 18, and 20-year-olds) the development of the processing components underlying visual search for pop-out targets was tracked. Participants indicated the presence or absence of color or orientation feature singleton targets. Observers also solved a detection task, in which they responded to the onset of search arrays. There were two main results. First, analyses of inter-trial effects revealed differences in the search strategies of the 6-year-old participants compared to older age groups. Participants older than eight years based target detection on feature-less dimensional salience signals (indicated by cross-trial RT costs in target dimension change relative to repetition trials), the 6-year-olds accessed the target feature to make a target present or absent decision (cross-trial RT costs in target feature change relative to feature repetition trials). The result agrees with predictions derived from the Dimension Weighting account and previous investigations of inter-trial effects in adult observers (Found & Müller, 1996; Müller et al., 1995). The results are also in line with theories of cognitive development suggesting that the ability to abstract specific visual features into feature categories is developed after the age seven years. Second, overall search RTs decreased with increasing age in a decelerated fashion. RT differences between consecutive age groups can be explained by sensory-motor maturation up to the age of ten years (as indicated by RTs in the onset detection task). Expedited RTs in older age groups (10-, vs. 12-year-olds; 14- vs. 16-year-olds), but also in the 6- vs. 8-year-olds, are due to the development of search-related (cognitive) processes. Overall, the results suggest that the level of adult performance in visual search for pop-out targets is achieved by the age of sixteen.